Self-Efficacy And Communication Strategies For Blind Disability Entrepreneurs In Increasing Business Independence - Fachmi Ibrahim; Tarsani; Resman Maharul Tambunan; Nachua Biyan Aprita; Al Maidatuz Zuhruf (Yayasan Inovasi Kemajuan Intelektual, 2022)
The limited accessibility of information, technology, and public perception is an obstacle in developing the entrepreneurship of business actors with visual disabilities. Therefore, it is essential to explore communication strategies that can increase the involvement and independence of the visually impaired in the business world, especially the development of Al-Quran braille as part of literacy. This research aims to analyse self-efficacy and explore effective entrepreneurial communication strategies for the visually impaired, focusing on increasing their engagement and independence in business. Another goal is understanding the challenges the visually impaired face in business communication. This research method uses a qualitative approach by conducting in-depth interviews, observations, and document analysis of the visually impaired in entrepreneurship. This research resulted in a deeper understanding of self-efficacy and effective entrepreneurial communication strategies for the visually impaired. Positive self-efficacy can help determine the proper coping techniques to cope with the stress they are experiencing. In addition, this study found that effective communication strategies are essential to improve business independence for people with visual disabilities. These strategies include communicating positively, openly, and optimistically and emulating the spirit of achievement shown by friends with visual disabilities. The research provides practical guidance for the visually impaired who want to be involved in the business world and provides insight for business people and the general public to create an inclusive environment for the visually impaired in entrepreneurship in Al-Quran braille literacy.